What do you do when the binomial cannot value real options? The LSM model - S. Alonso Azofra; G. De La Fuente (Cogent Economics & Finance, 2014)
The Least-Squares Monte Carlo model (LSM model) has emerged as the derivative valuation technique with the greatest impact in current practice. As with other options valuation models, the LSM algorithm was initially posited in the field of financial derivatives and its extension to the realm of real options requires considering certain questions which might hinder understanding of the algorithm and which the present paper seeks to address. The implementation of the LSM model combines Monte Carlo simulation, dynamic programming and statistical regression in a flexible procedure suitable for application to valuing nearly all types of corporate investments. The goal of this paper is to show how the LSM algorithm is applied in the context of a corporate investment, thus contributing to the understanding of the principles of its operation.
Keywords: G31; G0; A; G3; 330; capital budgeting|investment policy; general; general economics and teaching; corporate finance and governance